Minds at war: dual mindset theory and the psychology of Europe’s descent into the First World War - Tchalakov, M (2017)
Discrepancies in how leaders and political elites react to the escalation of international crises and to the possibility of war, even when confronted with the same or similar international constraints and decision-making dilemmas, is a puzzling phenomenon not comfortably accounted for by either traditional rational actor or earlier ‘cognitive miser’ psycho-dynamic models. A new psychological theory — the dual mindset theory — suggests that the mindsets of individual leaders act as an intervening variable that can help to account for these puzzling discrepancies and, thereby, to explain certain historical paradoxes as they concern variation in war and peace outcomes in international affairs. According to the dual mindset theory, individual mindsets can be broadly categorised into two basic types: reflexive and reflective. The dominance of a reflexive mindset implies the rapid operation of intuitive, and often emotional, thought processes that are automatically performed as a reflex, or without much conscious thought. By contrast, the dominance of a reflective mindset implies the application of conscious, effortful deliberations that attempt to restrain the impulsive and rapid thought processes of the former without getting rid of them altogether. As they relate to decisionmaking in international relations, reflexive mindsets are hypothesised to increase the probability of aggression and conflict breaking out, while reflective mindsets are hypothesised to reduce this probability. Our dual mindsets are hypothesised to originate from two very different but interconnected systems of the human brain that provide the foundation for all human reasoning. These systems have been variously labelled as ‘Systems 1 and 2’, ‘automatic and effortful reasoning’ and, more popularly, ‘blinking and thinking’. These mindsets, and the dual systems of the brain from which they originate, are proposed to contribute to the observed variation in war and peace outcomes in international relations through the influence of three causal mechanisms: sensitivity to threats, propensity for risk and temporal discounting. The dual mindset theory is applied to the historical puzzle of why the First World War broke out when it did in the summer of 1914, during a relatively calm period of European politics, and not in response to earlier pre-war crises, in particular the Balkan Wars of 1912-1913, when the European continent appeared to be on the brink of conflict.